Foundations of high impact entrepreneurship - Zoltán J. Ács (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
This survey reviews the theoretical literature on high impact entrepreneurship. The survey is guided in part by the recent classification changes at the Journal of Economic Literature (JEL) regarding entrepreneurship. The board voted to create a new classification code, L26, for entrepreneurship. The JEL intends to use this code for all articles and books that focus on economic questions related to entrepreneurial activity. Publications related to questions on occupational choice issues will be cross classified with J23; those focusing on innovation and entrepreneurship will be cross classified with O31; those focusing on finance will be cross classified with G24 Investment Banking, venture capital, brokerage and rating agencies; those focusing on new firms, start ups; and business related publications on how to be an entrepreneur will be cross classified (or solely classified) with M13. What does this economic literature tell us about entrepreneurship? In order to answer the questions this review covers the intersection of entrepreneurship with labor markets, innovation and capital marketsthe three pillars of high impact entrepreneurship.
Keywords: L26; O31; J23; G24; 330; Entrepreneurship; high impact firms; occupational choice; innovation; finance; policy; leveraged startups; Unternehmer; Unternehmensgründung; Theorie; Publikationsanalyse; USA